Perspectives on social justice among US historic preservation practitioners: roles, actions and organisational responsibilities. Issue 6 (3rd June 2022) - Velez, Anne-Lise K.; Daniel, Joseph; Hoxha, Sara
ABSTRACT: This paper examines practitioner perspectives on responsibilities and organisational actions and towards social justice issues in the field among 75 historic preservation practitioners from across the United States. Respondents are representatives of organisations that are formerly partners of the National Trust for Historic Preservation or are affiliated with the National Preservation Partners Network as of 2020. A survey of historic preservation practitioners finds that just over half of organisational leaders agree their organisation has a role in ameliorating social justice issues. Content analysis of open-ended survey questions on current actions and their organisational responsibilities towards social justice reveals distinct categories of response among the participants, with notable overlap but some distinction between actions and responsibilities. Findings contribute to scholarship on preservation by documenting current organisational engagement and practitioner approaches to social justice by active preservationists with a breadth and depth of experience. Findings are useful for practitioners in moving beyond recommendations by scholars or overarching national organisations to yield an overview and provide benchmarking of the scope of activities and aims of U.S. preservation organisations across regions in relation to social justice issues.